Aberrant brain structural-functional coupling and structural/functional network topology explain developmental delays in pediatric Prader-Willi syndrome. - Huang, Zhongxin; Zheng, Helin; Wang, Longlun; Ding, Shuang; Li, Rong; Qing, Yong; Peng, Song; Zhu, Min; Cai, Jinhua (European Child & Adolescent Psychiatry, 2025)
Prader-Willi syndrome (PWS) is a neurodevelopmental disorder characterized by dysplasia in early life. Psychoradiology studies have suggested that mental and behavioral deficits in individuals with PWS are linked to abnormalities in brain structural and functional networks. However, little is known about changes in network-based structural-functional coupling and structural/functional topological properties and their correlations with developmental scales in children with PWS. Here, we acquired diffusion tensor imaging and resting-state functional magnetic resonance imaging data from 25 children with PWS and 28 age- and sex-matched healthy controls, constructed structural and functional networks, examined intergroup differences in structural-functional coupling and structural/functional topological properties (both global and nodal), and tested their partial correlations with developmental scales. We found that children with PWS exhibited (1) decreased structural-functional coupling, (2) a higher characteristic path length and lower global efficiency in the structural network in terms of global properties, (3) alterations in classical cortical and subcortical networks in terms of nodal properties, with the structural network dominated by decreases and the functional network dominated by increases, and (4) partial correlation with developmental scales, especially for functional networks. These findings suggest that structural-functional decoupling and abundant structural/functional network topological properties may reveal the mechanism of early neurodevelopmental delays in PWS from a neuroimaging perspective and might serve as potential markers to assess early neurodevelopmental backwardness in PWS.